Analysis of Conflict Management of Emotional Maturity Towards Women Married at a Young Age - Maharani Agustina, Shabrina Zahra Aminudin , Ubaidillah , Aniqotuzzuhro' Wish (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2024)
The emotional immaturity experienced by couples who marry early tends to cause conflicts in their households, especially in women. Therefore, it is important to understand conflict management in marriage settlement. This study aims to determine the emotional maturity of women who get married at a young age in domestic conflict management. This study uses a descriptive qualitative approach and sample takers use purposive sampling with the criteria of Women who are married in Sempu district, Banyuwangi regency Have been married for a maximum of 1 year, Aged a maximum of 20 years. So that five participants were obtained who had met these criteria. The results of the study show that in the management of domestic conflicts of women who marry at a young age, there are three common types, namely accommodation, collaboration, and avoiding conflict. Emotional maturity plays an important role in effective conflict management. Women who marry at a young age can show good emotional maturity if they can cope well with problems and have a supportive environment.